Ladybird Readers Beginner Level - Willy and Harry (ELT Graded Reader) - Pitts,Sorrel (Ladybird, 2021)
Ladybird Readers is an ELT graded reader series for children aged 3-11 learning English as a foreign or second language. The series includes traditional tales, popular characters, modern stories, and non-fiction. Beautifully illustrated and carefully written by language learning experts, the series combines the best of Ladybird content with the structured language progression that will help children develop their reading, writing, speaking, listening and critical thinking skills. The eight levels follow the Common European Framework of Reference for language learning (CEFR) and include language activities that provide preparation for the Cambridge English Pre-A1 to A2 (YLE) tests. Visit the Ladybird Readers website for more information. The unique code provided in each printed book will provide access to audio, extra activities and learning resources. Willy and Harry, a Beginner level Reader, helps children to learn and practice their first words in English. It introduces everyday phrases and focuses on vocabulary that young children can use in daily life. Simple text and repetition support understanding, and speaking and listening activities develop confidence. "I am sad," Willy says. "I want a friend. Are we friends?"